American farming culture and the history of technology - Brinkman, Joshua T. (New York, NY : Routledge, 2024)
"Presenting a history of agriculture in the American Corn Belt, this book argues that modernization occurred not only for economic reasons but also because of how farmers use technology as a part of their identity and culture. Histories of agriculture often fail to give agency to farmers in bringing about change and ignore how people embed technology with social meaning. This book, however, shows how farmers use technology to express their identities in unspoken ways and provides a framework for bridging the current rural-urban divide by presenting a fresh perspective on rural cultural practices. Focusing on German and Jeffersonian farmers in the 18th Century and Corn Belt producers in the 1920s, the Cold War, and the recent period of globalization, this book traces how farmers formed their own versions of rural modernity. Rural people use technology to contest urban modernity and debunk yokel stereotypes and women specifically employed technology to resist urban gender conceptions. The book shows how this performance of rural identity through technological use impacts a variety of current policy issues and business interests surrounding contemporary agriculture from the controversy over genetically modified organisms and hog confinement facilities to the growth of wind energy and precision technologies. Inspired by the author's own experience on his family's farm, this book provides a novel and important approach to understanding how farmers' culture has changed over time, and why machinery is such a potent part of their identity. This book will be of great interest to students and scholars of agricultural history, technology and policy, rural studies, the history of science and technology and farming culture in the USA"--
Chapter 1. Setting the stage: the genealogy of contemporary rural identity in the Midwest -- Chapter 2. Are we ready for this? Urban industrialism, rural resistance, and rural-urban conflict -- Chapter 3. The future of an idea: farmers use of technology to perform rural capitalistic modernity -- Chapter 4. Mother and radio: combatting urban gender stereotypes through technology use -- Chapter 5. Rumbling down main street: cold war ideology and the American way encouraging rural capitalistic modernity -- Chapter 6. We feed the world: rural globalized ultramodernity -- Chapter 7. The district of hicks: persistent urban views of farmers as backward -- Chapter 8. Inborn innovators or hog house janitors? the acceptance or rejection of technologies and rural globalized ultramodernity -- Chapter 9. Company in the combine: gender, farming, and comparing organic reformist and rural ultramodern identities -- Chapter 10. There they go again: understanding clashes between ultramodern farmers and organic advocates over food policy and reform
Keywords: Agricultural machinery -- Social aspects -- Middle West -- History; Farmers -- Middle West -- Social conditions; Middle West -- Social conditions -- History; SCIENCE / History; TECHNOLOGY / Agriculture / General